Safety climate strength: The negative effects of cliques and negative relationships in teams. (June 2021) - Arizon Peretz, Renana; Luria, Gil; Kalish, Yuval; Zohar, Dov
Highlights: The current study uses network analysis to study safety climate in cliques. Cliques were found to be a valid level of analysis for safety-climate research. The number of cliques in a team was negatively related to the team's safety-climate strength. Abstract: Safety climate is one of the most valid predictors of safety outcomes in organizations. Safety climate studies usually refer to formal organizational units (the team/department) as the main level of analysis for predicting climate emergence and safety outcomes. The current research extends the traditional perspective toward safety climate by proposing a complementary framework based on social network theory. Specifically, this research aims to understand how two common features of formal units, namely (1) the presence of informal subgroups of friends (i.e. cliques), and (2) the prevalence of negative relationships between team members, affect the team's safety climate strength. We hypothesized that employees who are members of cliques would exhibit high internal agreement, at the clique level, regarding the team's safety climate, and that both the number of cliques and the prevalence of negative relationships in a team would be negatively related to team safety-climate strength. We sampled 568 workers in 118 cliques within 46 formal teams in nine organizations. Findings showed the cliques to be a valid meso level of analysis for safety-climate research. The number of cliques in a team was negatively related to the team's safety-climate strength. In addition, we found an interaction effect between the number of cliques and the prevalence of negative relationships in the team, such that the negative association between the number of cliques and climate strength grew stronger as the prevalence of negative relationships increased.